A clinical study of trends of ectopic pregnancy and its management in a tertiary care hospital - Puttaraju, Chandana M.; Prasad, Nagothi Nagendra; Sailakshmi, M. P. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Ectopic gestation is a gynaecological emergency which culminates in pregnancy loss and causes significant maternal morbidity, mortality besides jeopardizing future conception. The study discusses the incidence, risk factors, symptomatology and management of ectopic pregnancy in a tertiary care teaching hospital. Methods: This was a prospective study of 45 cases of ectopic pregnancies at a tertiary care teaching hospital from January 2012 to December 2013. Information was collected in a structured proforma, tabulated and descriptive analysis was carried out. Results: The incidence of ectopic pregnancy was 1.17%. Majority of the patients (80%) belonged to 20-30 yrs age group. Second gravidas predominated (42.2%). Fallopian tube was the most common site (95.5%). Rudimentary horn ectopic accounted for 4.65%. Previous abdominopelvic surgery (31.1%), IUCD usage (22.2%), PID (20%), abortions (20%), tubectomy (15.5%) were the principal risk factors. 42% of the patients had no risk factor. The triad of amenorrhea, bleeding per vaginum and abdominal pain was seen in 51.1% of cases. Ultrasound, UPT, β-hCG estimation were the diagnostic tools. Ruptured ectopic pregnancy accounted for 64.4%. Nearly 95.5% of patients underwent surgery; salpingectomy (76%). Methotrexate was successful in 4.44%. There was no maternal mortality. Conclusions: Mostly diagnosis, prompt surgical or medical management is cornerstone of treatment. Primary prevention such as improved access to family planning services, sex education, treatment of STI, PID, surgical asepsis and haemostasis, implementing legislation for dispensing MTP drugs ameliorate risk factors and hence reduce ectopic pregnancy.